2013
DOI: 10.1155/2013/283941
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Porous Gelatin Composite Containing Naringin for Bone Repair

Abstract: As Gu-Sui-Bu (GSB) is a commonly used Chinese medical herb for therapeutic treatment of bone-related diseases, naringin is its main active component. This study elucidates how various concentrations of naringin solution affect the activities of bone cells, based on colorimetric, alkaline phosphatase activity, nodule formation, and tartrate-resistant acid phosphatase activity assays to determine the optimal concentration of naringin. GGT composite was obtained by combining genipin cross-linked gelatin and β-tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…The most effective concentrations were 1 and 10 lg/mL; at these levels naringin significantly improved osteoblastic cell differentiation by 50% (Chen et al 2013).…”
Section: In Vitromentioning
confidence: 92%
See 3 more Smart Citations
“…The most effective concentrations were 1 and 10 lg/mL; at these levels naringin significantly improved osteoblastic cell differentiation by 50% (Chen et al 2013).…”
Section: In Vitromentioning
confidence: 92%
“…The abilities of GGT and GGTN to repair bone defects were then evaluated. Radiographic analysis revealed greater new bone in-growth with the GGTN composite group compared with the GGT composite group at the same implantation time point (Chen et al 2013). Naringin has also been incorporated into electrospun nanoscaffolds containing poly (e-caprolactone) (PCL) and poly (ethylene glycol)-block-poly (e-caprolactone) (PEG-b-PCL).…”
Section: Controlled Release Formulationsmentioning
confidence: 92%
See 2 more Smart Citations
“…Naringin has been found to enhance the alkaline phosphatase level of osteoblastic MC3T3‐E1 cells (Jeong et al ., ) and the differentiation and maturation of rat calvarial osteoblasts (Zhai et al ., ). A recent study showed that gelatin composite containing naringin enhanced the osteoclast activity of mixed bone cells (Chen et al ., ). In vivo , naringin has been found to protect against ovariectomy‐induced bone loss in mice, which might be mediated through ligand‐dependent activation of oestrogen receptors in osteoblastic cells (Pang et al ., ).…”
Section: Introductionmentioning
confidence: 97%